Strategies to harmonize urbanization and flood risk management in deltas - Willem Oosterberg; Camiel Van Drimmelen; Maarten Van der Vlist (European Regional Science Association (ERSA), 2005)
In many countries, important economic centres and major cities are located in a flood-prone area at the confluence of a large river and the sea. The expansion of these cities increases the risk of major flood disasters, a risk that is further increased if the predicted effects of climate change come true. Recent thinking about flood prevention stresses the importance of restricting city expansions into flood-prone areas, flood-proofing cities and accomodating floods by reserving space for water. These ideas require innovative city design, cooperation between city planners and water managers, and a policy that connects various levels of government with business and the public. The choice of strategy may be culture-specific, but will in any case involve large investments, and have long-term and large-scale consequences. Thus, it is worthwhile to exchange experiences between delta's that are tackling this problem. In the paper we will compare the approaches in a number of "typical" urbanized flood-prone delta's: New Orleans in the Mississippi delta, the Randstad in the Rhine delta, Venice in the Po delta, Wuhan along the Yangtze, Yokohama along the Tsurumi, Dhaka in the Ganges-Brahmaputra delta and London along the Thames.
Keywords: 330